2016
DOI: 10.3945/ajcn.115.110700
|View full text |Cite
|
Sign up to set email alerts
|

Malnutrition risk in hospitalized children: use of 3 screening tools in a large European population

Abstract: Background: Several malnutrition screening tools have been advocated for use in pediatric inpatients. Objective: We evaluated how 3 popular pediatric nutrition screening tools [i.e., the Pediatric Yorkhill Malnutrition Score (PYMS), the Screening Tool for the Assessment of Malnutrition in Pediatrics (STAMP), and the Screening Tool for Risk of Impaired Nutritional Status and Growth (STRONG KIDS )] compared with and were related to anthropometric measures, body composition, and clinical variables in patients who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
106
4
14

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 127 publications
(139 citation statements)
references
References 27 publications
15
106
4
14
Order By: Relevance
“…Also, the tools failed to identify some malnourished patients, but the authors found a significant association between risk of malnutrition and longer hospital stays. For these reasons, the authors concluded that no nutritional risk screening tool available today can be indicated for routine use in pediatric hospitals [49].…”
Section: Nutritional Screening Tools For Pediatric Patientsmentioning
confidence: 99%
“…Also, the tools failed to identify some malnourished patients, but the authors found a significant association between risk of malnutrition and longer hospital stays. For these reasons, the authors concluded that no nutritional risk screening tool available today can be indicated for routine use in pediatric hospitals [49].…”
Section: Nutritional Screening Tools For Pediatric Patientsmentioning
confidence: 99%
“…Chourdakis et al 18 found that risk classification varied with tools and concluded that they were unable to recommend the current tools for use in clinical practice. In their study they only considered children who scored as high risk to be at risk and found that on a number of occasions those with subnormal BMI were not identified by the tools 18.…”
Section: Discussionmentioning
confidence: 99%
“…In their study they only considered children who scored as high risk to be at risk and found that on a number of occasions those with subnormal BMI were not identified by the tools 18. We, however, considered those who scored either medium or high risk to be at risk in our analysis, as those who were medium risk required ongoing monitoring and would be expected to pick up children with a suboptimal BMI who did not score as high risk.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations